Case Report: Novel NIPBL Variants Cause Cornelia de Lange Syndrome in Chinese Patients - Peng, Ying; Liang, Changbiao; Xi, Hui; Yang, Shuting; Hu, Jiancheng; Pang, Jialun; Liu, Jing; Luo, Yingchun; Tang, Chengyuan; Xie, Wanqin; Wang, Hua (Frontiers in Genetics, 2021)
Cornelia de Lange syndrome (CdLS) is a genetic disorder characterized by multisystemic malformations. Mutation in the NIPBL gene accounts for nearly 60% of the cases. This study reports the clinical and genetic findings of three cases of CdLS from unrelated Chinese families. Clinically, all the three cases were classified as classic CdLS based on the cardinal (distinctive facial features and limb malformations) and suggestive (developmental delay, growth retardation, microcephaly, hirsutism, and etc.) manifestations. SNP array detected a novel de novo heterozygous microdeletion of 0.2 Mb (arr[GRCh37]5p13.2(36848530_37052821)×1) that spans the first 43 exons of NIPBL in the fetus with nuchal translucency thickening in case 1. Whole-exome sequencing in family trios plus Sanger sequencing validation identified a de novo heterozygous NIPBL c.5566G>A (p.R1856G) mutation in the fetus with intrauterine growth retardation in case 2, and a novel de novo heterozygous NIPBL c.448dupA (p.S150Kfs*23) mutation in the proband (an 8-month-old-girl) in case 3. The cases presented in this study may serve as references for increasing our understanding of the mutation spectrum of NIPBL in association with CdLS